THE EFFECTIVENESS OF THE CONTEXTUAL TEACHING AND LEARNING MODEL IN IMPROVING STUDENTS’ CONCEPTUAL UNDERSTANDING - Rochim, Roudhoutul Aulia; Fitri Mughiroh, Ainun; Wulandari, Desi; Af’idah, Noer; Wijayadi, Andri Wahyu (Edukasi: Jurnal Pendidikan, 2026)
This study aims to analyze the effect of the application of the Contextual Teaching and Learning (CTL) learning model to enhance pre-service science teachers’ conceptual understanding in physics materials. This study uses a pre-experimental method with a one group pre-test post-test design. The instrument used was a test of concept comprehension ability. The results showed a significant effect in students' conceptual understanding with a t-test result of 3.922 (< 0.05). Based on the calculation of N-Gain, there were 12 students (40%) who experienced an increase in conceptual understanding in the medium category, and 18 students (60%) in the high category. The average N-Gain value of 0.73 shows that the increase in students' understanding of concepts on temperature and heat materials is relatively high. Thus, the results report that the CTL learning model is effective in improving students' understanding of concepts and is suitable for application in the physics learning process.